2021
DOI: 10.3390/cancers13235973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Biomarkers for Early Identification of Patients with Intracranial Metastatic Disease

Abstract: Nearly 30% of patients with cancer will develop intracranial metastatic disease (IMD), and more than half of these patients will die within a few months following their diagnosis. In light of the profound effect of IMD on survival and quality of life, there is significant interest in identifying biomarkers that could facilitate the early detection of IMD or identify patients with cancer who are at high IMD risk. In this review, we will highlight early efforts to identify biomarkers of IMD and consider avenues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Interestingly, a study by Bogsrud et al 23 reported detection of small satellite tumors of 2 to 4 mm in patients with suspected high-grade gliomas. All these tumors had high TBRs 4–18 that probably enabled detection below PET spatial resolution. The satellite tumors were undetectable on MRI, although this may be explained by the 5 to 14 days delay between MRI and PET/CT examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study by Bogsrud et al 23 reported detection of small satellite tumors of 2 to 4 mm in patients with suspected high-grade gliomas. All these tumors had high TBRs 4–18 that probably enabled detection below PET spatial resolution. The satellite tumors were undetectable on MRI, although this may be explained by the 5 to 14 days delay between MRI and PET/CT examinations.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Stereotactic radiosurgery (SRS) is frequently the preferred treatment for patients with brain metastases, but whole-brain radiation therapy, neurosurgical resection, and/or systemic treatments such as chemotherapy, immunotherapies, and targeted therapy can also be considered. 7,8 Late diagnosis may limit treatment options, 9 and early identification and accurate localization of brain metastases are therefore important for treatment planning and preventing further deterioration of the patient. 10 Precise tumor delineation and tools to differentiate brain metastases from treatment-related changes, such as radiation necrosis, are also of high importance.…”
mentioning
confidence: 99%
“…Previous research has identified several risk factors specific for the presence of BrMs in NSCLC: being the female gender; concurrent lymphatic metastases; specific microRNA signatures; a high neutrophil to lymphocyte (NLR) ratio; elevated levels of neurofilament light chain; presence of EGFR driver mutation; and elevated serum levels of CEA, S100B, ProApolipoprotein A1 (apo A-1), Ki-67, VEGF-C, caspace-3, and calcium. [25][26][27][28][29][30][31][32][33][34][35][36][37] Sun, et at., have even postulated that ProApolipoprotein A1 and S100B alone may be used for an independent and accurate diagnosis of metastatic brain tumors; which could allow a clinician performing metastatic work ups to administer prophylactic treatments, such as intracranial irradiation. [25] Preclinical studies using rodent models have demonstrated early detection of BrMs by employing molecular MRI with contrast agents that highlight tumor vascular factors ALCAM21 and VCAM-1.…”
Section: Introductionmentioning
confidence: 99%
“…Elegant studies have been designed to identify cancer biomarkers or signatures of indicating how patients would respond to therapies [ 1 , 2 ]. These previous studies aim to diagnose malignancy or to examine the prognosis such as future metastasis or long-term survival.…”
Section: Introductionmentioning
confidence: 99%